Intervening early in bipolar disorder in young people: a review of the clinical staging model. (16th January 2015) - Power, P.
Abstract : Bipolar disorder (BPD) essentially has its onset during adolescence and early adulthood. It has the capacity to be highly disruptive, dislocating individuals from their normal developmental trajectory and potentially causing significant long-term co-morbidity and chronicity. At a societal level the burden created is greater than schizophrenia. This is not helped by the very substantial delays in its diagnosis and appropriate treatment. Thus, there is a clear rationale for intervening earlier and at a younger age. However, the field of early intervention in BPD is in its infancy. One approach that conceptually provides a basis for early intervention is the Clinical Staging Model (used widely in general medicine). This article outlines how this model helps in an understanding of the emerging stages of BPD. It also summarises the interventions that might be appropriately introduced if a person progresses from an early to a late stage of the illness. Early intervention has a well-established record in psychotic disorders. If it can be realised for BPDs, then it may hold out hope of better outcomes for the next generation of young people at risk.